Analysis of Digital Workflow in Implantology - Gustavo Vargas da Silva Salomão; Eliseo Pablo Chun; Renato dos Santos Panegaci; Fernando Toledo Santos (Case Reports in Dentistry)
Digital workflow is increasingly accessible in daily dental practice. It has several benefits in implantology, such as the possibility of precise planning, which results in faster and safer surgery and, consequently, reduced prosthetic complications. There are also disadvantages that must be taken into consideration for successful treatment, such as deviations between the planned and placed implant position and intraoral scanning inaccuracies. We report a clinical case in implantology in which digital workflow was used throughout the process, pointing out its facilities and complications in the daily practice of dental surgeons. The patient had grade II mobility and external root resorption of tooth 11. After virtual planning, a surgical guide was fabricated by a CAD/CAM system, with immediate placement of a dental implant using the guided surgery technique. At the end of the osseointegration period, intraoral scanning was performed for fabrication of the final prosthesis also by a CAD/CAM system. After placement, the patient approved the aesthetic and functional results of the implant. We observed advantages such as simplification of clinical steps and safety of the proposed planning, but there were also disadvantages such as the complexity of digital tools, deviations of the placed implant, and inaccuracy in color selection. It was concluded that digital workflow is a reality that can be integrated into daily dental practice, resulting in greater safety, predictability of results, and ease of use in all clinical stages. However, it should be noted that there are still inaccuracies in digital tools and that a steep learning curve is needed in this area, which, if neglected, may lead to unsatisfactory results.